2015
DOI: 10.2337/dc15-1498
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Glucagon for Treatment of Insulin-Induced Hypoglycemia in Adults With Type 1 Diabetes: A Randomized Crossover Noninferiority Study

Abstract: OBJECTIVETreatment of severe hypoglycemia with loss of consciousness or seizure outside of the hospital setting is presently limited to intramuscular glucagon requiring reconstitution immediately prior to injection, a process prone to error or omission. A needle-free intranasal glucagon preparation was compared with intramuscular glucagon for treatment of insulin-induced hypoglycemia.RESEARCH DESIGN AND METHODSAt eight clinical centers, a randomized crossover noninferiority trial was conducted involving 75 adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
120
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(126 citation statements)
references
References 20 publications
2
120
0
Order By: Relevance
“…A previous randomized study in adults with T1D showed that 3‐mg NG was non‐inferior to 1‐mg intramuscular glucagon in treating insulin‐induced hypoglycaemia in a hospital setting 5. Another study in young people with T1D found that NG and injectable glucagon demonstrated similar glycaemic responses 8.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous randomized study in adults with T1D showed that 3‐mg NG was non‐inferior to 1‐mg intramuscular glucagon in treating insulin‐induced hypoglycaemia in a hospital setting 5. Another study in young people with T1D found that NG and injectable glucagon demonstrated similar glycaemic responses 8.…”
Section: Discussionmentioning
confidence: 99%
“…Nasal glucagon (NG), a needle‐free, single‐use, compact, portable, drug‐device combination consisting of 3 mg dry glucagon powder that does not require reconstitution, is currently under development as a rescue medication for severe hypoglycaemia 1. NG (3 mg) produced a rapid increase in blood glucose (BG) levels and was non‐inferior to intramuscular glucagon (1 mg) in a previous study in adults with insulin‐induced hypoglycaemia 5. The aim of the present study was to evaluate the real‐world effectiveness, tolerability and ease of use of NG (3 mg nasal glucagon; Eli Lilly and Company) in the treatment of moderate and severe HEs in adults with T1D.…”
Section: Introductionmentioning
confidence: 99%
“…In Fig. 2 of the study (1), it is clear that before 30 min, the probability of success was lower for intranasal glucagon. As per the data in that figure, the probability for success at minute 15 for intramuscular glucagon was 86% as compared with 71% for the nasal glucagon.…”
mentioning
confidence: 92%
“…Diabetes Care 2016;39:e192 | DOI: 10.2337/dc16-0955 Rickels et al (1) report the results of a randomized crossover noninferiority study, making the firm assertion that intranasal glucagon was highly effective in treating insulin-induced hypoglycemia in type 1 diabetes. Unfortunately, the methods described in their article fail to support such a strong claim.…”
mentioning
confidence: 99%
“…The data reported by the authors under ref. 41 [6] are the result of the efforts of that company together with the T1D registry in adults, while evidence of a positive effect of intranasal glucagon on children and adolescents had been published earlier [2]. Due to its simple use, if intranasal glucagon could be brought to the market and to regular use, it might represent a universal remedy for hypoglycemia in children, adolescents, and adults with type 1 diabetes and in all insulin-treated patients with diabetes.…”
mentioning
confidence: 99%